"Weak" C-H•••S interaction drives enantioselectivity in cinchona alkaloid complex catalyzed thiocyanation - Banerjee, Subhrashis; Vanka, Kumar (Chemistry-An Asian Journal, 2023)
The great success of asymmetric organocatalysis has made it one of the most important advancements made in chemistry in the past two decades. A significant achievement in this context is the asymmetric organocatalysis of the thiocyanation reaction. In the current study, computational studies with density functional theory have been done in order to understand an interesting experimental finding: the reversal of enantioselectivity from R to S when the electrophile is changed from beta-keto ester to oxindole for the thiocyanation reaction with the cinchona alkaloid complex catalyst. The calculations reveal an unusual fact - the principal reason for the reversal is the presence of the C-H center dot center dot center dot S noncovalent interaction, which is present only in the major transition states in each of the two nucleophile cases. Only recently has it been realized that the supposedly weak C-H center dot center dot center dot S noncovalent interaction has the properties of a hydrogen bond, and the fact that this interaction is the cause of enantioselectivity has relevance, because of the large number of asymmetric transformations involving the sulphur heteroatom.
Keywords: Density functional calculations; Enantioselectivity; noncovalent interactions; organocatalysis; reaction mechanisms